The Contribution of Teacher Pedagogical Competence to Children's Learning Interest in Taud At-Tartil - Siti Nur Afifah; Kun Nurachadijat (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
Pedagogic competence is the ability to manage student learning which includes the teacher’s understanding of student characteristics which also greatly influences children’s interest in learning. Form the teacher’s pedagogical competence we can have and see a big picture of the ability of an educator to develop the abilities and potential of his students. The purpose of this discussion is to understand the importance of teacher pedagogic competence which can be a reason for students’ interest in learning. Apart from that, with this competence educator are also able to provide appropriate learning for students to make it easier for them to accept new lessons and they can easily apply them in everyday life. The method used is literature review which seeks references from various books and journal articles in order to get the right theory so that conclusions are in accordance with the reality in the field. In addition to the literature, the research also conducted a source triangulation in order to obtain a research result that is relevant and in accordance with the conditions in the field. As for the results of his study, it can be said that the teacher’s pedagogical competence is very influential on students learning interest, because there is a special understanding of the method and how to overcom and understand what the child wants. So we can conclude tha an educator has an extraordinary responsibility, not only providing education they are aldo required to relearn and add insight about the world of education, especially for individual educators, especially in their competence. So tha it can be a motivation for education and motivate student to always be enthuasiastic in pursuing their goals and developing their potential. Keywords: Interes Pedagogic Competence, Motivation